Visual media in motion: Conceptualizing the short video format within visual platforms - Guerra, Giulia Isabella (AoIR Selected Papers of Internet Research, 2026)
Social media have become increasingly visually focused with the rise of visual-centric platforms like Instagram and TikTok, reshaping aesthetics and user experience. In these mobile-first spaces, vertical short videos redefined digital storytelling, content creation, and engagement. Although their relevance has fostered a rich and expanding body of research, a conceptualization of “short videos” remains elusive, with varying terminology across studies. Moreover, research on visual communication has extensively focused on static images, while missing conceptual work with respect to moving images designed for mobile consumption. Developing a conceptual framework is therefore essential, providing the foundation for systematically analyzing these audiovisual artifacts. Drawing from format theory, social media studies, multimodality and visual communication, this work introduces a conceptualization of short videos as a distinctive media format, defined by structural characteristics that allow to distinguish and analyze them across platforms. This work outlines the technical infrastructure and audiovisual features of the format, discussing how the interplay of diverse modes of communication fosters both collective and individual experiences, thereby shaping meaning making. This conceptual framework expands research on moving images in mobile environments, offering a comprehensive understanding of the role of short videos within visual and social media culture and supporting methodologies to examine their multimodal components.